Eurycoma longifolia Elevates Testosterone Levels in Androgen-Deficient Osteoporosis Rat Model - Eman Elgalfat (AlQalam Journal of Medical and Applied Sciences, 2025)
Osteoporosis is a chronic, progressive illness characterized by low bone mass and strength of the bone, resulting in increased risk of bone fracture. Testosterone replacement therapy (TRT) is one of the main treatments for male osteoporosis. However, TRT causes side effects, mainly prostate cancer and liver dysfunction. So, an alternative agent is required. This study was conducted to determine the effects of Eurycoma Longifolia (EL) on serum testosterone in orchidectomized rats, the androgen-deficient osteoporosis model. Thirty-two male Sprague Dawley rats were divided into 4 groups, with 8 rats in each group, which followed different treatments for 6 weeks, namely the sham-operated group, orchidectomized-control group, orchidectomized group and treated with EL (15 mg/kg), and orchidectomized group and treated with testosterone (8 mg/kg). Body weights of rats were taken weekly, and blood samples were taken before and after treatment to measure serum testosterone using the Testosterone ELISA technique. The result showed that EL and testosterone therapy have led to an increase in rat body weights. The levels of testosterone in the serum were considerably higher (p < 0.05) for the orchidectomized group treated with testosterone compared to the orchidectomized control and sham group. The orchidectomized group treated with EL also showed a significant increase in serum testosterone (p < 0.05) compared to the same group before treatment, but there was no significant difference between the other groups. In conclusion, EL treatment was successful in raising the level of serum testosterone in orchidectomized rats